Las normas de convivencia social y las reglas de los juegos de roles en los niños del inicial II de la escuela de educación básica IV Centenario en el periodo lectivo 2018 - Galarza Valarezo, Maura Estefania (2018)
The present work of investigation frames in a study titled, The norms of social coexistence and the rules of the games of roles in the children of the initial II of Basic Education IV Centenary School, 2018 school year. Whose problematic reference that the children of Initial II present norms of social coexistence that do not conform to the social rules: they not respect the rules of the game, the space of each boy in the develop activities, not to thank, not greet, to enter and to leave without requesting permission, not knowing how to apologize, do not comply with the instructions given by the teacher and social norms on their own initiative. Inside the objectives set out in the research are the general objective: To improve coexistence through the appropriation of the rules of social coexistence through the rules of role plays in the children of the initial II of Basic Education IV Centenary School in 2018 school year, which was fulfilled by designing an alternative proposal. We carried out a scientific-social, descriptive research with a quantitative-qualitative approach and participatory action, using different methods and instruments such as: scientific, inductive and descriptive method. The instruments used were: observation guide, survey. One of the mentioned conclusions is After the process of intervention in the rules of social coexistence and the rules of role plays, it allows the improvement of the children in the home and in the school with an adequate communication and discipline response.